STRATEGI PENINGKATAN PEMASARAN MELALUI PELATIHAN FOTO PRODUK PADA UMKM DI DESA SETILING KABUPATEN LOMBOK TENGAH - Moh. Taqiuddin; Baiq Yulfia Elsadewi Yanuartati; Baiq Rika Ayu Febrilia; Diswandi Diswandi; Ni Made Wirastika Sari; Idiatul Fitri Danasari (Universitas Mataram, 2023)
The MSME group in Setiling Village is in Central Lombok Regency. This group focuses on the processing and marketing of traditional herbal products, chayote chips, ant sugar and fern chips. So far, MSMEs in Setiling Village are still carrying out marketing activities in a conventional way targeting community buyers in the village. As a result, these marketing activities have not been optimal and have not been supported by the use of technology regarding the importance of producing good product photos. This service aims to improve marketing strategies for MSMEs in Setiling Village, Central Lombok Regency through product photo training. This product photo activity was carried out using the participant's smartphone. The main target in this activity is MSME actors who have received training and assistance in 2022. The method used in this community service activity is interactive participatory. Service is divided into three stages, namely planning and preparation, implementation and evaluation. Participants in the service activity consisted of 14 MSME actors and three students. At the beginning of the activity, participants were given material regarding the importance of product photos in marketing. Participants were also given an understanding of product photography techniques and product photo examples as a reference. After the material delivery activity, the participants then directly practiced the knowledge gained using their smartphones. During practical activities participants can use the property brought by the service team. Based on the activities that have been carried out, participants already have an understanding of product photo techniques and are able to produce product photos using their smartphone. Thus, there was an increase in participants' understanding of marketing strategies. Another result is that participants managed to upload product photos to their e-commerce accounts.